Investigation of electrostrictive polymers for energy harvesting - Liu, Yiming (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2005)
The recent development of electrostrictive polymers has generated new opportunities for high-strain actuators. At the current time, the investigation of using electrostrictive polymer for energy harvesting, or mechanical to electrical energy conversion, is beginning to show its potential for this application. In this paper we discuss the mechanical and electrical boundary conditions for maximizing the energy harvesting density and mechanical-to-electrical coupling of electrostrictive materials. Mathematical models for different energy harvesting approaches were developed under quasistatic assumptions. Energy harvesting densities then are determined for representative electrostrictive material properties using these models. Comparison with a magnetic-based energy harvesting system suggests that electrostrictive energy harvesting systems are preferable for "small" energy harvesting applications with low-frequency excitation